The Assessing the Role of Price, Advertising and Product Quality in Shaping Purchase Decisions: Insights from Converse Users in Jabodetabek - Sovania, Erina; Iksan, Zainuri (Dinasti International Journal of Management Science, 2024)
This study aims to analyze the influence of price, advertising, and product quality on the purchase decisions of Converse shoes in the Jabodetabek region. Primary data were collected through questionnaires distributed to 100 respondents selected using accidental sampling. Data analysis was performed using SmartPLS software. The results indicate that price does not significantly impact the purchase decision of Converse shoes. In contrast, advertising and product quality have a significant influence on purchase decisions. These findings highlight the critical role of effective advertising and high product quality in shaping consumer decisions, ultimately enhancing the competitive advantage and market position of Converse products.